Comparison between diagnostic performance of intestinal Fusobacterium nucleatum, Bacteroides fragilis and Escherichia coli in 5-fluorouracil resistance to colorectal cancer: A meta‑analysis. (2022) - Wang, Wen-Yu; Zhou, Hang; Wang, Zhi; Zhang, Yu-Hang
Highlights: F. nucleatum test showed better discrimination ability for detecting 5-FU resistance in CRC patients as compared with B. fragilis and E. coli . CRC patients with 5-FU resistance have approximately 2.57 times higher possibility of testing positive F. nucleatum compared with subjects without 5-FU resistance, as well as 52% chance of an CRC individual having 5-FU resistance if the test of F. nucleatum is negative. Abstract: Background: Intestinal Fusobacterium nucleatum ( F. nucleatum ) infection has been implicated into the progression of colorectal cancer (CRC). However, F. nucleatum as a biomarker in 5-fluorouracil (5-FU) resistance of CRC has not been fully analyzed by comparing with other types of gut microbiota. In order to further reduce the random error and bias of individual research, this meta‑analysis aimed to compare the diagnostic performance of intestinal Fusobacterium nucleatum, Bacteroides fragilis and Escherichia coli in 5-FU resistance to colorectal cancer and provide evidence‑based data to clinical practice. Methods: Comprehensive searches of PubMed, Embase, Cochrane Library and Web of Science databases were conducted. A total of 11 studies were selected according to the preestablished inclusion and exclusion criteria and analyzed by Review Manager 5.4 software, which included mapping of forest plots, heterogeneity tests, meta‑regression, sensitivity analysis and publication bias. Results: Overall sensitivity and specificity of F. nucleatum detection in 5-FU resistance of CRC were 0.65 (95% CI:0.60–0.69) and 0.70 (95% CI:0.59–0.87), respectively. Its positive likelihood ratio (PLR) and negative likelihood ratio (NLR) in detecting colorectal cancer were 2.57 (95% CI:1.47–3.21) and 0.52 (95% CI:0.43–0.63). The diagnostic odds ratio (DOR) was 4.92 (95% CI:2.23–7.33), which significantly exceeds the performance of B. fragilis (DOR: 0.53, 95% CI:0.31–0.82) and E. coli (DOR: 0.63, 95% CI: 0.57–0.76) for indicating 5-FU resistance of CRC. Conclusion: Compared with intestinal B. fragilis and intestinal E. coli, intestinal F. nucleatum is more reflective of 5-FU resistance to colorectal cancer.